INTERATING MOMENT IN THE NURSING COURSE: A STRATEGY TO SHAPE POTENTIAL RESEARCHERS - Ivete Palmira Sanson Zagonel (Universidade Federal do Paraná, 2005)
The study is a result of the experience lived along three school semesters during the implementation of the subject Integrating Moment in the course of Nursing which is a part of the school curriculum from the first term of the course in six consecutive terms. Its goal is to review the perceptions and meanings regarding the subject Integrating Moment to the students of nursing during the process of their learning; to identify from what has been learned, subsidies for the improvement of the teaching-learning strategies. It is a descriptive-exploratory research with qualitative approach. Sixty-eight nursing students have participated. I have used the open-ended questionnaire, which the student had to answer and hand in together withthe Term of Informed Consent signed. I have followed thesteps of analysis of Bardin ́s contents using thematicanalysis. Two Units of Context and six Units of Meaning were used. The comprehension of the analysis of the statements indicates the perception of the students as a moment of interaction, insertion, integration,interdisciplinary knowledge, information union, besides creating options, discovering, clearing doubts, going further, communicating, educating and boosting knowledge. It has been shown to be a potential instrument of the investigative spirit that is the basis of professional education and future performance.